ASSESSMENT OF READINESS OF GONDOKUSUMAN SUB-DISTRICT IN FILLING INTEGRATED PALLIATIVE CARE FOR OLDER PEOPLE - Wilianto, Maria G; Perdamaian, Teguh K; Sigilipoe, Mitra A; Widagdo, M M (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Background : Every year the number of elderly people in Indonesia continues to increase. In 2018 the highest number of elderly people was in the DI Yogyakarta Province, amounting to 12.37%. Data from Riskesdas showed that 51.28% of the elderly experienced health complaints and 25.99% of the elderly experienced illness. This can reduce the patient's quality of life. Therefore, integrated palliative care is needed for the elderly to improve the quality of life for patients and their families in dealing with health problems. Palliative care already exists in 5 hospitals in 5 regions in Indonesia, namely DKI Jakarta, DI Yogyakarta, Surabaya, Denpasar, and Makassar.Objective : The general objective of this study was to explore the readiness of Gondokusuman District in fulfilling integrated palliative care for the elderly.Method : This study used a thematic analysis research design. The research sample was 46 respondents. The data is taken from previous research entitled "Mapping Community Assets Related to Health and Social Services for the Elderly in Yogyakarta City in 2019".Result : An overview of health-related policies was found, such as the Chronic Disease Management Program (Prolanis), the Health Social Security Administration (BPJS), and Supplementary Food Provision (PMT). However, no policy description regarding palliative care has been found. A description of the availability of drugs was found which included prescribing, distribution and financing. Educational programs and content found in the form of education through counseling and counseling. Resources found are in the form of health infrastructure, community infrastructure, and human resources. However, there is no culture related to integration either vertically or horizontally.Conclusion : There is a description of health-related policies, availability of medicines, educational programs and content, and resources that support palliative care in Gondokusuman District. However, no specific policies have been found regarding palliative care and integration.Keyword : Policies, Drug Availability, Educational Programs and Content, Resources, Integration